2015
DOI: 10.1194/jlr.m055798
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of fatty acid binding protein aP2 from adipocytes through a nonclassical pathway in response to adipocyte lipase activity

Abstract: Journal of Lipid Research Volume 56, 2015 423Adipose tissue is an endocrine organ whose products orchestrate the metabolic functions of various tissues, including brain, pancreas, and liver, to maintain systemic homeostasis. Adipocytes respond to metabolic and immune cues by mobilizing their fat stores through lipolysis and by secreting a variety of hormones and cytokines ( 1, 2 ). Such signals converge on target tissues, for example on liver to regulate glucose production, and on ␤ cells to modulate insulin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
172
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(187 citation statements)
references
References 64 publications
12
172
0
Order By: Relevance
“…For example, lipolysis has been linked to increased FABP4 secretion from adipose tissue via a nonclassical mechanism (59,60,187,188). FABP4 secretion is regulated by ATGL and hormone-sensitive lipase activity and subsequent increase in fatty acid availability (60). Interestingly, there is strong correlation between circulating FABP4 levels and metabolic disease in preclinical models and in humans (59,(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199).…”
Section: Therapeutic Potential Of Targeting Inflammatory Lipids In Mementioning
confidence: 99%
See 2 more Smart Citations
“…For example, lipolysis has been linked to increased FABP4 secretion from adipose tissue via a nonclassical mechanism (59,60,187,188). FABP4 secretion is regulated by ATGL and hormone-sensitive lipase activity and subsequent increase in fatty acid availability (60). Interestingly, there is strong correlation between circulating FABP4 levels and metabolic disease in preclinical models and in humans (59,(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199).…”
Section: Therapeutic Potential Of Targeting Inflammatory Lipids In Mementioning
confidence: 99%
“…Reciprocally, pro-inflammatory cytokines such as TNF regulate lipid metabolism in adipocytes via increasing lipolysis (58), which continuously exposes the organs to fatty acids. Increased lipolysis from adipose tissue is also linked to secretion of the adipokine, aP2 (FABP4) (59,60), which is an important mediator of immunometabolic responses locally at the adipose tissue, and links the lipolytic state to glucose metabolism in the liver and elsewhere (61)(62)(63). Overall, while adipocytes are the specialized site for neutralizing fatty acids, this capacity is not infinite and these cells are not impervious to excess lipid accumulation, which drives inflammatory responses locally and at distant tissues.…”
Section: Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are membrane vesicles that carry a cargo of proteins, lipids and nuclear acids, which may differ based on adipogenic stages and/or under pathological conditions [120,121,122]. Adipocyte-secreted exosomes are demonstrated to contain specific transcripts (such as adiponectin [123] and aP2 [124]) and miRNAs [119,99], which are transported into recipient cells and are involved in modulating gene expression as well as energy metabolism. Several studies demonstrated that adipocyte derived exosomes mediate cell-cell communication that might play a role in controlling lipogenesis and cell size [121], obesity related disease [120] and nonalcoholic fatty liver disease [125].…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…, and James Cantley 3 Dear Editor: We read with interest the recent paper "Circulating Adipocyte Fatty Acid-Binding Protein Induces Insulin Resistance in Mice In Vivo" by Kralisch and Kl€ oting et al (1). The authors concluded that exogenous administration of the adipokine Adipocyte Fatty Acid Binding Protein (AFABP/FABP4/aP2) for 8 weeks caused insulin resistance in mice, measured indirectly using the HOMA-IR score, which is based on a composite of circulating glucose and insulin levels.…”
mentioning
confidence: 98%